The property right to exclude: a right in need of reinforcement? - Abeyratne, M.D.M. (Faculty of Law, University of Colombo, 2021)
Property impacts on political, social, and economic aspects of human life, throughout history and across nations. Testifying to property's singular importance are multifarious property theories occupying a large conceptual space in scholarly work not limited to law. Within this gamut exists attributes of ownership pivotal to conceptualizing property. Widely accepted is that ‘right to exclude’, an entitlement to exclude unwanted persons from private property, is a cornerstone of ownership attributes essential for efficient use of property, and foundational to the in rem nature of property rights. Despite its importance ‘the right to exclude’ is often narrowed in the public interest in modern governance. This paper focuses on research hypotheses that (1) eviscerating right to exclude results in economic cost to owners; and (2) strengthening right to exclude enhances economic efficiency to owners. It examines narrowing of right to exclude in Sri Lanka using legislation, and case law on servitudes and encroachments. South African property jurisprudence is studied as residuary property law in both countries is received Roman-Dutch law, though constitutional protection of property in South Africa since 1996, is noted as a change agent. It draws on the June 2021 US Supreme Court case of Cedar Point Nursery et al v Hassid et al where under constitutional protection of private property rights a 1975 California regulation granting right of access to unions to enter properties of agricultural landowners to meet workers was struck down as contravening owner right to exclude. Constitutional property analysis remains pertinent since Sri Lanka contemplates constitutional change, with givens of firstly, its Supreme Court's reflection in Soysa v Arsecularatne decrying judicial expansion of Roman- Dutch law to meet new contexts, and secondly, its Constitution's nineteenth amendment granting right to information, and throwing into relief proprietary nature of information. Since interdisciplinary research is mandated, the analytical tool of law and economics is used to consider economic efficiency of narrowing right to exclude. As the literature review reveals, on both counts the paper is original research in Sri Lanka. This exploratory research shows narrowing right to exclude leads to downturn in economic efficiency of property, a matter which policy makers need to consider.
Keywords: property; right to exclude; economic efficiency